SHAPING ISLAMIC HIGHER EDUCATION IN RIAU’S MALAY CONTEXT IN THE THOUGHT OF HAJI ZAINI KUNIN - Tambak, Syahraini; Sukenti, Desi; Yasin, Muhammad Muthi’ul Haqq bin Fatah; Yasin, Muhammad Dhiya’ul Hafidh bin Fatah; Zakaria, Gamal Abdul Nasir (State Islamic University North Sumatra, 2025)
While much research has explored the development of Islamic higher education, the contributions of Malay figures remain underexamined. This study investigates the development strategies of Islamic higher education through the perspective of Zaini Kunin, a prominent Malay scholar. This study a historical approach, the research involved interviews, literature analysis, and focus group discussions, analyzed through thematic identification, source criticism, interpretation, and historiography. The findings highlight Zaini Kunin’s method, which includes: (1) constructing an Islamic scientific framework based on Surah Al-Qashash [28]:77 across four domains—religious sciences, natural and social sciences, social ethics, and environmental sciences; (2) affirming tauhidullah (the creed of Oneness of God) as the ultimate goal; (3) embedding Islamic values in the curriculum; (4) developing sincere and committed human resources; (5) promoting social piety; and (6) fostering national and international collaboration. In conclusion, Zaini Kunin’s method for developing Islamic higher education is rooted in the foundational philosophy of Islam, as drawn from its core teachings.